Human Capital and Information and Communication Technology Nexus: The South African Perspective - Mongale, Itumeleng Pleasure; Lethabo Magongoa, Mahlatse Malebo (Journal of Reviews on Global Economics, 2020)
Despite the fact that South Africa invests a considerable amount in education and also the fact that black youth have higher educational attainment now than at any point in history, education which is seen as a process, the outcome of which is general knowledge and human capital is still facing enormous challenges. Using the bounds testing procedure, the study investigated the human capital and information and communication technology (ICT) nexus in South Africa. This was achieved by regressing investment in ICT and ICT infrastructure variables on one of the human capital variables (education). The literature review has revealed that studies on this issue using time series analysis are relatively thin in the context of South Africa. The results revealed that gross fixed capital formation (ICT equipment) has positive relationship with human capital whereas both the mobile cellular subscriptions per 100 people and fixed telephone subscriptions per 100 people have a negative relationship with human capital in South Africa. The policy implication of this study is that economic policies should recognise the importance of ICT in the development of human capital by bringing utilisation of ICT to some far-off locations within a country, to boost human capital development.